2020
DOI: 10.1155/2020/1360197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Used Motor Oil and Bitumen as Additive on the Permeability and Mechanical Properties of Low Plastic Soil

Abstract: Stability of permeable soils near large-scale water reservoirs for paved and unpaved road pavements is all too frequently compromised due to excessive seepage and the climatic conditions of that area. In this research, a multilevel research approach was adopted by conducting a comparative study of the microspectroscopy through Fourier transform infrared (FTIR) spectra to investigate the maximum absorbance correlation along with mechanical investigations (such as the compressive strength, modified proctor test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…The results showed that oil pollution led to the deterioration of the geotechnical properties of the soil samples. Compared with raw soil, its maximum dry density, optimum water content, permeability, and shear strength decreased [6][7][8]. The particle size distribution and density of soil samples have a great impact on the mechanical properties and permeability of oil-contaminated clayey silt.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that oil pollution led to the deterioration of the geotechnical properties of the soil samples. Compared with raw soil, its maximum dry density, optimum water content, permeability, and shear strength decreased [6][7][8]. The particle size distribution and density of soil samples have a great impact on the mechanical properties and permeability of oil-contaminated clayey silt.…”
Section: Introductionmentioning
confidence: 99%
“…[8]. Soil stabilization states to the exercise of modifying a natural soil's structure, by physical and/or chemical alteration techniques, such that it is able to achieve definite engineering requirements [9]. In the present era, waste material is given preference in the stabilization of soil.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, stone dust is pozzolanic in nature and includes coarse particles not seen in other admixtures such as fly ash. Numerous research studies were carried out for soil stabilization, the results show the significant positive impact of waste on soil properties [9]. Since, we are in the contemporary industrial age, with the fast development in the industrial zone, we must look for new additive materials, including modern wastes that will enhance our wellbeing while simultaneously causing negative consequences such as health issues and pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [23] and Li et al [24] performed an unconfined compressive strength test to study the strength and deformation characteristics of oil-polluted coastal saline soil samples by mixing oil with coastal saline soil of known water content. Iqbal et al [25] carried out a series of laboratory tests to study the permeability and mechanical properties of low plastic soil. Based on the abovementioned studies, the physical-mechanical behaviors are relatively complex for different types of soil, such as finegrained soil, clay, and kaolin soil.…”
Section: Introductionmentioning
confidence: 99%